ANALISIS RETURN ON INVESTMENT (ROI) PROGRAM SERTIFIKASI PROFESIONAL SEBAGAI INSTRUMEN EVALUASI INVESTASI SDM DI BANK RAKYAT INDONESIA CABANG TUBAN - Nurul Fauziyah; Novi Vizainiyah; Anjar Sulistyowati; Ahmad Mudzakkir (J-MACC, 2026)
This study evaluates the Return on Investment (ROI) of two professional certification programs at Bank Rakyat Indonesia Tuban Branch—Teller Certification (STB) and Anti-Money Laundering/Counter-Financing of Terrorism (AML/CFT)—using the Phillips ROI Methodology. Employing a mixed-methods explanatory sequential design, quantitative data from 23 participants were analyzed through cost-benefit analysis, impact isolation, and monetary conversion, while qualitative insights identified intangible benefits. The results show a substantial difference in ROI, with STB achieving 492% and a 2.4-month payback period driven by cross-selling revenue and efficiency gains, whereas AML/CFT yielded 34% ROI with a 35.5-month payback period, mainly reflecting its role in risk mitigation and regulatory compliance. Despite lower financial returns, both programs contributed significant non-financial benefits such as enhanced professional authority, knowledge standardization, and employee retention. This study highlights the distinction between “value-creating” and “value-protecting” certifications, offering a strategic framework for optimizing human capital investments in the banking sector.